Axial stiffness matrix of non-uniform Bernoulli-Euler bar element - Sulaeman, Erwin (IIUM Press, 2011)

(untitled)
This chapter describes the procedure to develop the axial stiffness matrix of beam element having arbitrary variation of axial stiffness distribution along its span. To obtain analytical formulation, the stiffness matrix is constructed from the flexibility matrix. A Bernoulli-Euler differential equation that relates the load and deformation angle derived first. The general rational function resulting from the integration of the Bernoulli-Euler is transformed to a simpler rational function using a minimum denominator rational function procedure.